Rapid Assessment of the Fatigue Limit Using an Iterative Algorithm Applied to Intrinsic Dissipation - Luca Santoro; Raffaella Sesana; Francesca Maria Curà (Engineering Proceedings, 2025)
The aim of this paper is to introduce and validate an iterative algorithm for the rapid assessment of the fatigue limit. The algorithm is based on the analysis of intrinsic dissipation and offers a more efficient alternative to traditional fatigue testing methods. An iterative method is applied to thermal data and dissipative data collected during cyclic loading tests. Passive thermography is used to monitor surface temperature increments, which are indicative of microstructural damage. The dataset is iteratively divided into regions above and below a hypothesized fatigue limit, and curve fitting is performed on each subset. The algorithm seeks to minimize the error between experimental data and the fitted curves, ensuring continuity at the estimated fatigue limit. The proposed iterative method provides a reliable and rapid estimate of the fatigue limit, significantly reducing the number of tests needed compared to conventional methods. The results demonstrate good agreement between predicted and experimental fatigue limits, particularly in additively manufactured materials with complex microstructures. This method offers a cost-effective and time-efficient solution for evaluating the fatigue performance of materials produced via additive manufacturing. It is especially useful in applications where rapid material characterization is required.